Adverse events with IL‐17 and IL‐23 inhibitors for psoriasis and psoriatic arthritis: a systematic review and meta‐analysis of phase III studies. (9th December 2019) - Loft, N.D.; Vaengebjerg, S.; Halling, A.‐S.; Skov, L.; Egeberg, A.
Abstract: Biologics targeting interleukin (IL)‐17 and IL‐23 are generally well‐tolerated and considered safe, though adverse events are seen more often compared with placebo. The objectives of this systematic review and meta‐analysis were to assess the prevalence of adverse events in patients with psoriasis or psoriatic arthritis with any adverse events after 12, 16, 24 and 52 weeks of treatment with IL‐17 or IL‐23 inhibitors. Two independent authors searched the databases PubMed and EMBASE for studies reporting on adverse events in phase 3 trials of IL‐17 and IL‐23 inhibitors for patients with psoriasis and psoriatic arthritis. The study was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Data synthesis was performed using a random‐effects model. In total, 44 publications (43 studies) were included in the analyses. The proportion of patients with any adverse events for all treatments pooled were 0.57 [95% confidence interval (CI): 0.55–0.59] after 12 weeks, 0.52 (95% CI: 0.49–0.55) after 16 weeks, 0.72 (95% CI: 0.66–0.78) after 24 weeks and 0.81 (95% CI: 0.76–0.86) after 52 weeks. Across therapies, the most prevalent AEs were infections, nasopharyngitis and headache. For ixekizumab one of the most prevalent AEs was injection site reactions, reported in 15.7% of the patients after 52 weeks. Overall, IL‐17 and IL‐23 inhibitors appear to be well‐tolerated with good safety profiles. Our findings may aid the clinical decision making when choosing the most appropriate therapy for patients with moderate‐to‐severe psoriasis.